فعالية استخدام وسيلة Fun Easy Learnلترقية إتقان المفردات العربية لدى طلاب الصف التاسع بمدرسة إحياء علوم الدين المتوسطة الإسلامية بنجربارو - Yuspa, Anida; Bahsin, Said Taufiqurrahman (STIT Darul Hijrah Martapura, 2025)
ABSTRACTThe learning of Arabic, particularly vocabulary, among ninth-grade students at MTs Ihya 'Ulumuddin Banjarbaru faces challenges in vocabulary mastery due to several factors. These include the use of traditional teaching methods by teachers especially the translation method a limited instructional time which reduces learning effectiveness, and the lack of variety in instructional media. This study aims to determine the effectiveness of using the Fun Easy Learn application in improving the vocabulary mastery of ninth-grade students at MTs Ihya 'Ulumuddin Banjarbaru. This research employs a quantitative approach and uses an experimental method. Based on the research data, the researcher concludes that the use of the Fun Easy Learn application significantly improves vocabulary mastery among ninth-grade students at MTs Ihya 'Ulumuddin Banjarbaru. A significant difference was found between the experimental class and the control class. The post-test average score of the control class was 76.18, while the experimental class scored 89.12. Based on the statistical result of p < 0.001, which is less than 0.05, it indicates that Ha is accepted and Ho is rejected. The conclusion of this study is that the use of the Fun Easy Learn application is effective in enhancing vocabulary mastery among ninth-grade students at MTs Ihya 'Ulumuddin Banjarbaru.Keyword : Fun Easy Learn Application, Vocabulary MasteryABSTRAKPembelajaran Bahasa Arab khususnya kosakata pada siswa kelas IX MTs Ihya ‘Ulumuddin Banjarbaru mengalami kekurangan dalam penguasaan kosakata yang disebabkan oleh beberapa faktor diantaranya metode yang digunakan oleh guru yang masih menggunakan metode tradisional, yang metode terjemahan,waktu pendidikan yang sempit sehingga pembelajaran kurang efektif, dan penggunaan media yang kurang beragam. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan Aplikasi Fun Easy Learn Dalam Meningatkan Penguasaan Kosakata Siswa Kelas IX MTs Ihya ‘Ulumuddin Banjarbaru. Penelitian ini menggunakan pendekatan Kuantitatif dan jenis penelitian Eksperimen. Berdasarkan hasil dari data penelitian, peneliti dapat menarik kesimpulan dari penggunaan Aplikasi Fun Easy Learn Dalam Meningkatkan Penguasaan Kosakata Siswa Kelas IX MTs Ihya ‘Ulumuddin Banjarbaru, yaitu Terdapat perbedaan yang signifikan antara kelas eksperimen dan kelas kontrol, dan diketahui bahwa nilai Post-test kelas kontrol dengan rata-rata 76,18 dan kelas eksperimen 89,12. Berdasarkan hasil data diatas <0.001 lebih kecil dari 0.05 berarti Ha diterima dan Ho ditolak. Kesimpulan pada penelitian ini bahwa penggunaan Aplikasi Fun Easy LearnDalam Meningatkan Penguasaan Kosakata Siswa Kelas IX MTs Ihya ‘Ulumuddin Banjarbaru efektif. Kata Kunci: Aplikasi Fun Easy Learn, Penguasaan Kosakata